(untitled) (Revista Rupturas, 2021)
Music scenes were the most influential expressions in Costa Rican popular culture at the end of the twentieth century. These cultural formations were facilitated by the public relevance of the youths, and the growth of cultural consumption and urban areas. Also, they were leaded by the rock and metal music; therefore, the purpose of this paper is to analyze the articulation and evolution of the metal urban scene of Costa Rica between the years 1980-1992. For that, this investigation will provide evidence of how the metal music separate himself from the rock music and set his own musical dynamic, although that generated public awareness.